Keterampilan berbicara ditinjau dari penguasaan kosakata dan sikap percaya diri peserta didik kelas V sekolah dasar - Gayatri Candra Kirana; Slamet Slamet; Tri Budiharto (Universitas Sebelas Maret, 2023)
Abstract. The purpose of this research was (1) vocabulary mastery wuth speaking skills, (2) selft-confident with speaking skill, (3) vocabulary mastery and self-confident with the speaking skills elementary school at grade 5TH Ahmad Yani Cluster, Cilacap Selatan District, Cilacap City. This study uses a quantitative correlation reaearch ,ethod. Sampling using cluster random sampling with a population elemtary school at grade 5TH students Ahmad Yani Cluster. The data analysis techniques used simple correlastion analysis and multiple correlastion assisted by Ms.Excel. The result of the simple correlation analysis indicate that the hypothesis states that there is a significant and positive reliationship between vocabulary mastery with speaking skilss. Based on the data analysis, it can be conclude of vocabulary mastery and speaking skills ry1 (0.798), the coefficient of the correlation was tested with the t test, the result tcount (11.011)> ttable (1.995) showing a significant correlation between the self confident and speaking skils ry2 (0.9129), the coefficient of the correlation was tested with the t test, the rusult tcount (18.580)> ttable (1.995) showing a significant correlation between both the vocabulary mastery and self-confident together with speaking skills ry12 (0.856). the coefficient the F test obtained Fcount = 92.907real level α = 0.05, with df = 68 obtained Ftable = 3.131, then Fcount > Ftable.